Maternal mortality by COVID-19 in Brazil - Alex Sandro Rolland Souza; Melania Maria Ramos Amorim
Abstract SARS-CoV-2, the new coronavirus of severe acute respiratory syndrome, which causes a predominantly respiratory disease called COVID-19, quickly caused a pandemic, due to its high transmissibility, leaving a trail of deaths around the world. Initially, the pregnancy puerperal cycle was not associated with complications and mortality, only later was recognized as a risk group. As the disease progressed, the maternal mortality rate by COVID-19 increased, Brazil is responsible for an important portion. This rate may be even higher due to underreporting, difficulties in performing laboratorial tests and possible false negative results and depends on the health policies adopted by each region or country. It is important to carry out studies on maternal mortality so that the prognostic factors can be recognized and so avoid them.